THE KOTOV-LYUTY EFFECT: THE NEW COSMOLOGICAL INVARIANT? - Larionov, M. G. (Одеські астрономічні публікації, 2017)
The analysis of the complete variation of the global constants using the world model with the positive cosmological constant, basis on radio astronomical data, was carried out. It was shown that, the simultaneous variations of the global constants are fulfilled in the limits of the self-confirmed solution, and the new cosmological invariant T = Λ/c appears. This allows to explain the existence of the 160-min period of the active galactic nuclei and quasars intensity variations independent of the redshift.